The Role of Organizational Culture in Enhancing Talent Retention in the Hybrid Work Era - Budiadi, Hasman; Dharmani, I Gusti Agung Aju Nitya; Nurhandayani, Henny (Universitas Syiah Kuala, 2025)
The COVID-19 pandemic accelerated the adoption of hybrid working models, where employees divide their time between remote and on-site work. While hybrid work offers flexibility and better worklife balance, it also introduces challenges such as digital fatigue, social isolation, and fairness concerns. Organizational culture emerges as a critical factor influencing employee engagement, loyalty, and retention in such contexts. This study aims to explore how cultural dimensionsparticularly fairness, inclusion, and support for worklife balanceaffect talent retention in hybrid environments. Using a qualitative literature study, data were collected from academic journals, books, and industry reports published within the last five years. The analysis employed a thematic content approach to synthesize findings and identify patterns linking organizational culture and retention outcomes. Results indicate that organizations fostering fairness and transparency in performance evaluations and workload distribution are more successful in reducing turnover intentions. Inclusion and belonging are equally vital in preventing remote worker isolation, while worklife balance initiatives help mitigate digital fatigue. Conversely, toxic or neglectful cultures significantly increase disengagement and attrition. The study concludes that organizational culture is not a peripheral factor but a strategic resource that strengthens loyalty and long-term commitment. Practical examples from companies such as Microsoft, Google, and Spotify illustrate how adaptive cultures support retention during hybrid transitions.